RNAi-based pest control: Production, application and the fate of dsRNA - He, Li; Huang, Yanna; Tang, Xueming (Frontiers in Bioengineering and Biotechnology, 2022)
The limitations of conventional pesticides have raised the demand for innovative and sustainable solutions for plant protection. RNA Interference (RNAi) triggered by dsRNA has evolved as a promising strategy to control insects in a species-specific manner. In this context, we review the methods for mass production of dsRNA, the approaches of exogenous application of dsRNA in the field, and the fate of dsRNA after application. Additionally, we describe the opportunities and challenges of using nanoparticles as dsRNA carriers to control insects. Furthermore, we provide future directions to improve pest management efficiency by utilizing the synergistic effects of multiple target genes. Meanwhile, the establishment of a standardized framework for assessment and regulatory consensus is critical to the commercialization of RNA pesticides